ANALISIS PENGARUH PRODUCT PLACEMENT TERHADAP WORD OF MOUTH ATAS MEREK SPEEDY PADA ACARA LIVE SHOW NBL INDONESIA - Jayanti, Alfitri; Jatmiko, Rohmat Dwi; Andharini, Sri Nastiti (Department of Management, 2014)
The research aims to analyze the effect of product placement on word of mouth at NBL Indonesia. Population is audience of NBL Indonesia. Sample taken were 100 respondents using purpossive sampling method. Simple Linear Regression used as an analytical tool. The result shows that product placement has a positive effect on word of mouth. Keywords: Product Placement, and Word of Mouth, NBL Indonesia